Pharmacognostic Investigation of Clerodendrum phlomidis Linn. f. Root - Dinesh Kumar; Ajay Kumar; Om Prakash (Journal of Tropical Life Science, 2014)
The present study was aimed to perform the pharmacognostic evaluation of Clerodendrum phlomidis Linn. f. root in terms of organoleptic, macro-microscopy, fluorescence analysis and physicochemical parameters. The characteristic macroscopic features showed that the root consists of 7-15 cm long, 0.2 -3.0 cm thick pieces which are cylindrical, tough and yellowish-brown externally, with hard fracture and slightly astringent taste. The main microscopic characters of the root shows exfoliating cork, having 10-15 rows of tangentially elongated, thick-walled cells. Cortex consists of round to oval parenchymatous cells, a few containing rhomboidal shaped calcium oxalate crystals. Endodermis consists of 3-4 layers of non-lignified, thick-walled rounded parenchymatous cells followed by a single pericyclic layer. Phloem consists of isodiametric, thin-walled, parenchymatous cells whereas xylem contains lignified pitted vessels. Medullary rays consisting of biseriate layer of lignified and radially elongated parenchymatous cells, is narrower in the xylem region while wider in the phloem region. Further, physicochemical analysis of the root power reports total ash, water soluble ash, sulphated ash as 7.8, 0.9 and 10.3 % w/w respectively. Successive extraction of the root powder with petroleum ether, chloroform, alcohol, water yielded 2.2, 2.4, 12.4 and 9.6 % w/w extracts respectively. Fluorescence study imparted characteristic colours to the root powder when observed under visible, short and long wavelength light. Various pharmacognostic parameters evaluated in this study helps in botanical identification and standardization of Clerodendrum phlomidis L. root part in crude form and provide the authentic data for the researchers and scientists involved in carrying out further research on this plant part.